Analisis Kebijakan Restorasi Ekosistem Gambut di Indonesia dengan Discourse Network Analysis - Alamsyah Alamsyah; Erlisa Saraswati; Rizky Ghoffar Ismail (Jurnal Ilmu Lingkungan, 2024)
After the forest fires in 2014-2016, the Government of Indonesia (GoI) placed the restoration of the peatland ecosystem (RPE) as one of its priority policies in the environmental sector. This study seeks to analyze RPE in Indonesia using a discourse network analysis approach. Researchers utilize Twitter as primary research data. This data was processed with R, rDNA, and Gephi. Researchers found three network patterns that are connected to RPE efforts in Indonesia. First, affiliate networks connect actors and the concepts voiced by the actors. This network involves various actors such as government institutions, civil society organizations, private corporations, universities, research institutes, foreign governments, international organizations, and local citizens. The dominant concept in the affiliate network is peatland restoration and multi-stakeholder collaboration. Second, the actor congruence network assigns Mangrove and Peatland Restoration Agency (Badan Restorasi Gambut dan Mangrove or BRGM) as the dominant and central actors. However, some actors are not connected to the core network and create separate sub-groups. Third, a network of conflicts between actors involving four conflict themes: Government Regulation Number 57/2016 concerning Amendments to Government Regulation Number 71/2014 on Protection and Management of Peatland Ecosystems, peatland conversion, horizontal conflicts between the local community and plantation corporations, and prevention and law enforcement related to forest fires. The researcher recommends BRGM to: (a) strengthen collaborative practices with the various parties involved in RPE; (b) beware in converting peatland so it does not damage the peatland ecosystem landscape; (c) integrate community conflicts with plantation corporations as part of the RPE agenda in Indonesia. The researcher also recommends NGO activists in Indonesia who care about peatlands to continue monitoring and criticizing the RPE process in Indonesia, and fight for local community groups that have been marginalized by the RPE process. Researchers also encourage plantation corporations, both oil palm plantations and industrial timber plantations, to jointly guard RPE in Indonesia by not opening up new land as part of the actual contribution of the Indonesian people to climate change adaptation and mitigation.